(untitled) (American Journal of Islam and Society, 2017)
In the recent past, fear, hatred, and hostility toward Islam and Muslims in the West have attracted increasing scholarly interest, a development that is certainly commendable. Some important works have delved deeply into the Western imagination and stereotyping of Islam and Muslims, among them John Victor Tolan’s Medieval Christian Perceptions of Islam (1996) and Saracens: Islam in the Medieval European Imagination (2002), Fredrick Quinn’s The Sum of All Heresies: The Image of Islam in Western Thought (2008), Matthew Dimmock’s Mythologies of the Prophet Muhammad in Early Modern English Culture (2013),1 and Sophia Rose Arjana’s Muslims in the Western Imagination (2015) ...